Human-Centered Software Engineering : 9th IFIP WG 13. 2 International Working Conference, HCSE 2022, Eindhoven, the Netherlands, August 24-26, 2022, Proceedings - International Conference on Human-Centered Software Engineering (9th : Eindhoven, Netherlands) 2022; Bernhaupt, Regina; Ardito, Carmelo; Sauer, Stefan (Cham, Switzerland: Springer, 2022)
This book constitutes the refereed conference proceedings of the 9th IFIP WG 13.2 International Conference on Human-Centered Software Engineering, HCSE 2022, which was held in Eindhoven, The Netherlands, during August 2022. The 11 full papers presented together with 2 poster and demo papers were carefully reviewed and selected from 25 submissions. The papers focus on the interdependencies between user interface properties and contribute to the development of theories, methods, tools and approaches for dealing with multiple properties that should be taken into account when developing interactive systems. They are organized in the following topical sections: user-centred design approaches; model-based and model-driven approaches; software development strategies; and posters and demos.
Includes author index.
Keywords: Software engineering; User-centered system design; Human-computer interaction